BUSINESS ETHICS AS A BASIS FOR DESIGNING THE VISION AND MISSION HOSPITALS: EMPIRICAL EVIDENCES FROM MUHAMMADIYAH HOSPITAL PONOROGO, INDONESIA - Anna Marina; Sentot Imam Wahjono (STIE Perbanas Surabaya, 2013)
This study aimed to identify business ethics practiced in hospital-based religious values as the basisfor designing the vision and mission. Designing was done by discussing business ethics found inthis research with the ethical and moral conceptsof Islam and Muhammadiyah. This research wasconducted at Muhammadiyah hospital. This studyused a qualitative approach to the phenomenological analysis techniques to process data collected through in-depth interview, outside observation, and relevant documentation. In-depth interviews carried out ten times for eleven key informants. Focus Group Discussion held twice for twenty-one executive employees. Observation wasdone for eleven times over a period of six months, including observation and interviews with tencustomers. Triangulation process is done by presenting the opinion of prominent figures in Muhammadiyah through his writing in several books onthe values of Muhammadiyah including basicideological struggle of the Muhammadiyah founder KH Ahmad Dahlan. Similarly, the theory ofIslamic Business Ethics findings are used to guide the Vision, Mission and then business ethicspracticed by the management and employees of Muhammadiyah Hospital.